Educational Game Design to Raise Awareness of Social Anxiety and Cognitive Behavioral Therapy - Syaikhhanun Nabila Az-Zahro'; Pratama Wirya Atmaja; Eva Yulia Puspaningrum (bit-Tech, 2025)
Social Anxiety Disorder (SAD) is a common yet often misunderstood mental health condition that significantly impacts the lives of adolescents and university students. Despite its prevalence, awareness and understanding of SAD and its evidence based treatment, Cognitive Behavioral Therapy (CBT), remain limited among young adults. This study aims to design and develop Social Survival, a 2D educational game intended to raise awareness of SAD and introduce CBT techniques through an interactive and engaging medium. The game is developed using the Unity engine and employs the Interactive Digital Narrative (IDN) framework to deliver a singleplayer narrative experience. It presents scenarios simulating SAD symptoms and embeds CBT strategi such as relaxation, cognitive restructuring, and exposure into gameplay via minigames. The development process included a needs analysis, general and detailed design phases, and implementation of mechanics aligned with CBT principles. To evaluate learning effectiveness, a pre-test and post-test were administered and analyzed using the N-Gain formula. Player satisfaction was assessed using the Game User Experience Satisfaction Scale (GUESS-18), which measures dimensions such as enjoyment, engagement, and educational value. The results indicate a positive improvement in player understanding of SAD and CBT, along with favorable user experience ratings. The study concludes that serious games can serve as effective tools for mental health education, although clinical treatment should still be guided by professionals.